Dysregulated miR-155 and miR-125b Are Related to Impaired B-cell Responses in Down Syndrome - Farroni, Chiara; Marasco, Emiliano; Marcellini, Valentina; Giorda, Ezio; Valentini, Diletta; Petrini, Stefania; D'Oria, Valentina; Pezzullo, Marco; Cascioli, Simona; Scarsella, Marco; Ugazio, Alberto G.; De Vincentiis, Giovanni C.; et al. (Frontiers in Immunology, 2018)
Children with Down Syndrome (DS) suffer from immune deficiency with a severe reduction in switched memory B cells and poor response to vaccination. Chromosome 21 encodes two microRNAs (miRs), miR-125b and miR-155, that regulate B-cell responses. We investigated the expression of miR-125b and miR-155 in B cell and T cell subsets and during B-cell activation in DS. The frequency of B-cell and T-cell subsets were analyzed in tonsils of HD and DS. We studied the expression of miR-125b and miR-155 in sorted tonsillar B-cell and T-cell subsets and after in vitro activation of PBMCs. We blocked miRs using antagomiRs and determined plasmablast formation in vitro. We found that the germinal center (GC) reaction was impaired in DS as GC size and numbers of GC B cells and TFH cells were severely reduced. The expression of miR-155 and miR-125b was increased in tonsillar memory B cells. MiR-125b was also higher than expected in plasma cells. The expression of miR-155 rose excessively upon in vitro stimulation of PBMCs with CpG, whereas miR-125b was constitutively over-expressed in DS. The increase of miR-155 and its functional consequences were blocked by antagomiRs in vitro. Our data show that the expression of human chromosome 21-encoded miR-155 and miR-125b is altered in B cells of DS both in vivo and in vitro. Administration of antagomiRs changes the fate of B cells in vitro, partially correcting the defects observed in DS. HSA21-encoded miRs may play a role also in DS-associated dementia and leukemia. Our study suggests that antagomiRs may represent pharmacological tools useful for the treatment of DS.